The Effect of Physical Cues on Customer Loyalty: Based on the Mediating Effect of Customer Engagement and Value Co-creation - Xin-Mei Ye; Hira Batool; Shi-Zheng Huang (Emerging Science Journal, 2023)
As a new business model, e-commerce live broadcasting has great value in the commercial field. Based on value co-creation theory and the stimulus-organic-response model, this study explores the influence of physical cues in e-commerce live broadcast scenes on customer loyalty. Using the audience of China's e-commerce live broadcasting platform as the research object, 404 valid data points were collected through a questionnaire survey, and a structural equation analysis model was adopted to explore the relationship among the physical clues of the e-commerce live broadcasting scene, customer engagement, value co-creation, and customer loyalty and to verify the mediating effect of customer engagement and value co-creation. The research shows that aesthetic appeal, layout, and function have a positive impact on customer engagement, but financial security has no positive impact on customer engagement. In addition, value co-creation has an intermediary effect, and customer engagement and value co-creation have a double intermediary effect on physical cues and customer loyalty in e-commerce live broadcast scenes. The research not only expands the theory of value co-creation and scene but also provides practical reference value for e-commerce live broadcasting platforms and enterprises and promotes the design of physical cues in e-commerce live broadcasting scenes to improve customer loyalty. Doi: 10.28991/ESJ-2023-07-04-020 Full Text: PDF